P287 Offline Fractional Exhaled Nitric Oxide and Breath Frequency. (12th November 2015) - Howard, C; MacBean, V; Lunt, A; Greenough, A
Abstract : Introduction/objectives: Fractional exhaled nitric oxide (FeNO) is a noninvasive method of assessing airway inflammation and recommended by NICE (2014) to aid asthma diagnosis and management. Offline measurement techniques demonstrate comparable results to online and are more practical in certain clinical settings, particularly in young children who struggle with online measurements. International guidelines (ATS/ERS 2005) recommend targets for pressure and flow but not for the number of breaths per sample. Young children may take multiple breaths to complete offline reservoir filling, but whether this influences results due to contamination of the sample with ambient gas from equipment deadspace has not been assessed. Our aims were to investigate the magnitude of such effects and form a predictive equation for how increasing breath number dilutes offline measurements. Methods: A prospective observational study was undertaken recruiting 20 volunteers aged 18–42 years (13 female). FeNO was measured online (Medisoft Exp'Air 2001) and offline following exhalation into a one-litre Tedlar bag using one, five or ten breaths to complete bag filling. Airway pressure was maintained above 5 cmH2 O to ensure velum closure and expiratory flow at 50 (+/-5) ml/s. Predicted percentages of offline FeNO relative to online were calculated by: 100 – ((equipment deadspace (53 mls) x no of breaths)/bag volume) *100 Predicted offline values were compared to measured. Results: The median (IQR) online FeNO in parts per billion (ppb) was 24 (14–30) ppb. There was a significant reduction in offline FeNO with increasing breath number (p < 0.0001). Median (IQR) offline FeNO of 1-breath (22 (15–32) ppb) was not significantly different to online FeNO (p = 0.51). Median (IQR) offline FeNO of 5-breaths was 16 (7–22) ppb and 10-breaths 13 (5–19) ppb, lower than online FeNO (p = 0.03 and p = 0.005 respectively). The predicted offline values are compared with measured offline values, expressed as a percentage of online, in Table 1. Conclusion: One-breath offline collection methods had comparable results to online FeNO measurements, but higher breath number resulted in lower values likely due to sample contamination with ambient gas and dilution of nitric oxide. These results suggest that multiple breaths should not be used to obtain an offline FeNO result.